Size structuring and allometric scaling relationships in coral reef fishes. (20th March 2017) - Dunic, Jillian C.; Baum, Julia K.
Summary: Temperate marine fish communities are often size‐structured, with predators consuming increasingly larger prey and feeding at higher trophic levels as they grow. Gape limitation and ontogenetic diet shifts are key mechanisms by which size structuring arises in these communities. Little is known, however, about size structuring in coral reef fishes. Here, we aimed to advance understanding of size structuring in coral reef food webs by examining the evidence for these mechanisms in two groups of reef predators. Given the diversity of feeding modes amongst coral reef fishes, we also compared gape size–body size allometric relationships across functional groups to determine whether they are reliable indicators of size structuring. We used gut content analysis and quantile regressions of predator size–prey size relationships to test for evidence of gape limitation and ontogenetic niche shifts in reef piscivores ( n  = 13 species) and benthic invertivores ( n  = 3 species). We then estimated gape size–body size allometric scaling coefficients for 21 different species from four functional groups, including herbivores/detritivores, which are not expected to be gape‐limited. We found evidence of both mechanisms for size structuring in coral reef piscivores, with maximum prey size scaling positively with predator body size, and ontogenetic diet shifts including prey type and expansion of prey size. There was, however, little evidence of size structuring in benthic invertivores. Across species and functional groups, absolute and relative gape sizes were largest in piscivores as expected, but gape size–body size scaling relationships were not indicative of size structuring. Instead, relative gape sizes and mouth morphologies may be better indicators. Our results provide evidence that coral reef piscivores are size‐structured and that gape limitation and ontogenetic niche shifts are the mechanisms from which this structure arises. Although gape allometry was not indicative of size structuring, it may have implications for ecosystem function: positively allometric gape size–body size scaling relationships in herbivores/detritivores suggests that loss of large‐bodied individuals of these species will have a disproportionately negative impact on reef grazing pressure. Abstract : Temperate aquatic ecosystems are often size‐structured, but little is known about the community properties of their tropical counterparts. The authors provide novel evidence that a subset of coral reef predators are size‐structured, with piscivores displaying gape limitation and ontogenetic niche shifts. Gape sizes and allometries also varied widely across coral reef different fish functional groups.